2020
DOI: 10.3389/fendo.2020.00452
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Preoperative Anti-thyroglobulin Antibody in Papillary Thyroid Cancer Between 2011 and 2015 in Beijing, China: A Retrospective Study

Abstract: The anti-thyroglobulin antibody (TgAb) has been suggested to be more common in patients with papillary thyroid cancer (PTC). Here, we performed a retrospective study investigated the correlation between TgAb level and PTC in Chinese patients between 2011 and 2015. Patients with goiter who underwent thyroidectomy and received a confirmed pathological diagnosis were enrolled into the study. Clinical characteristics and preoperative thyroglobulin antibody (TgAb) level data were collected from all enrolled patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
(44 reference statements)
5
12
2
Order By: Relevance
“…There were 535 (79.7%) patients with PTC in the TgAb-positive group and 2,154 (63.8%) with PTC in the TgAbnegative group. The prevalence of PTC was signi cantly higher in TgAb-positive patients than in TgAbnegative patients (13). Our result of consistently positive TgAb values of 21.6% and consistently negative TgAb values of 68% was similar to other reports.…”
Section: Discussionsupporting
confidence: 91%
“…There were 535 (79.7%) patients with PTC in the TgAb-positive group and 2,154 (63.8%) with PTC in the TgAbnegative group. The prevalence of PTC was signi cantly higher in TgAb-positive patients than in TgAbnegative patients (13). Our result of consistently positive TgAb values of 21.6% and consistently negative TgAb values of 68% was similar to other reports.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that thyroid autoantibodies were associated with better clinicopathologic features in children and adolescents with PTC. The possible potential mechanism was that TgAb could specifically recognize epitopes on the Tg of PTC patients to cause tumor epitope-specific immune responses, increase the destruction of cancer cells and exert its protective effect by regulating the tumor microenvironment ( 26 , 27 ). TPOAb may mediate by complement-mediated cell death and/or antibody-dependent cytotoxicity to exert its anti-cancer effect ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 13 15 Thyroid FNAC management was cost-effective compared with watchful management. 16 Several factors – such as age, 17 female sex, 18 thyroid status, thyroid hormone level, 19 thyroid autoantibodies, 20 metabolic syndrome components, 21 , 22 smoking and alcohol consumption, 23 environmental factors, 18 , 24 diet and nutritional pattern, 25 and genetic factors 26 – have been reported as risk factors associated with thyroid nodular diseases and cancers.…”
Section: Introductionmentioning
confidence: 99%